2012
DOI: 10.1152/ajpendo.00151.2012
|View full text |Cite
|
Sign up to set email alerts
|

Pyruvate uptake is increased in highly invasive ovarian cancer cells under anoikis conditions for anaplerosis, mitochondrial function, and migration

Abstract: Anoikis resistance, or the ability for cells to live detached from the extracellular matrix, is a property of epithelial cancers. The "Warburg effect," or the preference of cancer cells for glycolysis for their energy production even in the presence of oxygen, has been shown to be evident in various tumors. Since a cancer cell's metastatic ability depends on microenvironmental conditions (nutrients, stromal cells, and vascularization) and is highly variable for different organs, their cellular metabolic fluxes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 42 publications
3
78
0
Order By: Relevance
“…We showed that when O-ASC-secreted arginine is depleted (using L-arginase) or when O-ASC-secreted factors induced increased NO synthesis in cancer cells is inhibited (using L-NAME), there is a decline in the growth rate of both ovarian cancer and endometrial cancer cells. It was previously reported by our group that ovarian cancer cells secrete considerable amount of citrulline, thereby indicating high NOS activity and arginine utilization (33). Here, our data showed that ovarian cancer and endometrial cancer cells use arginine produced by O-ASCs and generate citrulline.…”
Section: Discussionsupporting
confidence: 69%
“…We showed that when O-ASC-secreted arginine is depleted (using L-arginase) or when O-ASC-secreted factors induced increased NO synthesis in cancer cells is inhibited (using L-NAME), there is a decline in the growth rate of both ovarian cancer and endometrial cancer cells. It was previously reported by our group that ovarian cancer cells secrete considerable amount of citrulline, thereby indicating high NOS activity and arginine utilization (33). Here, our data showed that ovarian cancer and endometrial cancer cells use arginine produced by O-ASCs and generate citrulline.…”
Section: Discussionsupporting
confidence: 69%
“…Consistent with the requirements, increased cancer invasiveness under deadherent conditions is associated with higher mitochondrial activity, elevated ATP production, pyruvate uptake, and oxygen consumption. 29 Surrounding stromal cells may facilitate the acquisition of a proinvasive metabolic profile. Under aerobic conditions, 15,16 Glucose utilization Glycolysis 1 Respiratory chain 17,18 Glutamine metabolism NADPH generation, oxaloacetate regeneration for the TCA cycle 10,11 Creatine synthesis for ATP regeneration 17 Peroxide Reduced production through mitochondrial hyperpolarization 9 Production essential for anchorage independence 17,[19][20][21][22] Outcome Biosynthesis 11 Overcome ATP deficit 18 to avoid anoikis 15 glycolysis is induced in mesenchymal stem cells adjacent to osteosarcoma cells.…”
Section: Metabolism Of Deadherent Cellsmentioning
confidence: 99%
“…These differences in metabolism would have an effect on cell migration, and pyruvate may be used by highly invasive ovarian cancer cells to migrate in attached conditions and, thus, may enhance metastatic potential. 35 The enzymes in glycolysis also play important roles in tumor migration and invasion. Phosphoglucose isomerase (PGI, also known as glucose-6-phosphate isomerase or phosphohexose isomerase) is a housekeeping cytosolic enzyme that catalyzes the conversion of glucose-6-phosphate into fructose-6-phosphate in the second step of glycolysis.…”
Section: How Does the Glycolysis Pathway Affect Tumor Cell Migration mentioning
confidence: 99%